Some Examples for the Automatic Generation of Self-Assessment Queries in Manufacturing Processes Engineering Subjects - Calvo, Felix; Andrés, Eva María; Sanz-Lobera, Alfredo; González, Ignacio (Materials science forum, 2017)
This paper presents different examples of automatic generation of queries to be implemented in a b-learning platform. Queries can be used as complementary contents and self-assessment by students in Manufacturing Processes subjects. They are useful when the available time for classroom teaching is reduced and also in blended applications, allowing students the consolidation of in-person received knowledge. Firstly, some considerations about the teaching of Manufacturing Processes subjects and about the types of queries to be generated automatically are explored. Secondly, a list of potential manufacturing topics for which this methodology is suitable is proposed, selecting three of them. Finally, and by means of non-specialized computer tools, an example of application is developed and the obtained results are presented in each topic.